Shibata Renzaburō and the Reinvention of Modernism in Postwar Japanese Popular Literature - Vorobiev, Artem (Springer International Publishing, 2022)
1. Introduction – 2. Early Life and and Formative Years – 3. War and Postwar Experience – 4. Fame: The Nemuri Kyōshirō Phenomenon – 5. Shibata Renzaburō's Other Works – 6. Conclusion. Shibata Renzaburō and the Reinvention of Modernism in Postwar Japanese Popular Literature explores the life and work of Shibata Renzaburō (柴田錬三郎, 1917–1978), the author of adventure and historical novels who was instrumental in reinvigorating popular Japanese literature in the postwar period. This book considers postwar Japanese society through the prism of Shibata’s writing, exploring how the postwar period under SCAP Occupation influenced Shibata’s writing and generated the extraordinary popularity of samurai fiction in the postwar era at large. Through the use of a nihilistic warrior, Nemuri Kyōshirō, and other samurai characters, Shibata Renzaburō addresses important social issues of the day, such as the trauma of defeat, postwar reconstruction, and the attending societal ills and neuroses, while keeping his literature entertaining and easy to read, which ensured its mass appeal in postwar Japan.
10.1007/978-3-031-11192-1
Keywords: Oriental literature.; Ethnology.; Culture.; Japan—History.; Motion pictures—Asia.; Literary form.